Relação entre a infecção por parasitos gastrointestinais e valores de hematócrito em pequenos ruminantes - Figueredo, Brenda Ferreira de. (Brasil, 2023)
Endoparasites are important causes of diseases in sheep and goats. The economic losses are due to the low productivity, usually observed in the dry period, and the high mortality, which occurs mainly at the end of the rainy season or the beginning of the drought. Resistance to antiparasitics appears because of mutations that arise spontaneously in any group of growing cells, exposed to drugs or not, most of the time, in a harmful way. The objective of the work was to compare the parasitic load of the animals and the hematocrit values in small ruminants raised in the semi-intensive system in Amazonas through hematocrit values and checking eggs per gram of feces (OPG). In five moments, feces were collected directly from the rectal ampoule of 19 animals (9 sheep and 10 goats) for OPG counting and blood sample collection by venipuncture of the jugular. It was possible to observe the inversely proportional relationship between hematocrit values and parasitic load of small ruminants, presenting a higher average parasitic load (OPG = 4,390) and lower mean hematocrit value (22.16% in goats and 27.25 in sheep) in the transition between rainy to dry period. Keywords: Gastroenteritis. Ruminants. Amazonas.